Efeitos da acupuntura a laser na modulação autonômica cardíaca em jovens adultos saudáveis: Uma revisão sistemática - Silva, Wendell Aguiar (2021)
The Autonomic Nervous System (ANS) perform an essential role in the control and balance of our body, for example, controlling the cardiovascular system. The need to explore the sympathomimetic and parasympathomimetic effects on the cardiovascular system has led to the development of quantitative markers of cardiac autonomic activity, with heart rate variability (HRV) being the most promising marker. Clinical evidence proposes that sensory nerve stimulated by acupuncture modalities, including laser acupuncture, is associated with excitatory or depressant effects on the cardiovascular system and it can be examined from changes in the High frequency and Low frequency variables. The purpose of this study was to evaluatethe evidence concerning the described effects of laser acupuncture on cardiac autonomic modulation in healthy young adults. The systematic review included search terms in MEDLINE electronic databases via PubMed, LILACS and Cochrane Library.Records of studies and protocols, gray literature, annals of scientific events and the database of theses and dissertations (CAPES) were also searched, in addition to manual search by checking the reference list of the articles included. There was no restriction on the year or language of publication. Randomized clinical trials (RCT) that compared laser acupuncture with placebo, with traditional acupuncture (needles) and with electromagnetic field were included.Two independent researchers contributed in study selection, data selection, assessment of risk of bias, and certainty of evidence. 73 studies were initially selected, but only 06 were included in the qualitative synthesis of this review. We included 188 patients and studies with sample sizes ranging from 13 to 56 patients, with approximately 85.10% men and 14.89% women. For outcome analysis, it was found that laser acupuncture had greater efficacy than comparators with effects described under heart rate variability in only two studies, these studies with the certainty of the evidence classified as very low.No adverse effects have been described. The present review concluded that laser acupuncture influences cardiac autonomic modulation when analyzed from the heart rate variability, however, when compared to other interventions, further studies are needed.